2006
DOI: 10.1016/j.neuropharm.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids at the spinal level regulate, but do not mediate, nonopioid stress-induced analgesia

Abstract: Recent work in our laboratories has demonstrated that an opioid-independent form of stress-induced analgesia (SIA) is mediated by endogenous cannabinoids [Hohmann et al., 2005. Nature 435, 1108. Non-opioid SIA, induced by a 3-min continuous foot shock, is characterized by the mobilization of two endocannabinoid lipidsd2-arachidonoylglycerol (2-AG) and anandamidedin the midbrain periaqueductal gray (PAG). The present studies were conducted to examine the contributions of spinal endocannabinoids to nonopioid SIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 59 publications
2
66
0
1
Order By: Relevance
“…Detailed study of this effect revealed the mobilisation of both AEA and 2-AG in the periaqueductal grey matter (111) , and suggested that 2-AG acting at CB 1 receptors was the predominant mechanism. Additional work indicated that further enhancing stress-induced EC signalling via FAAH or MAGL inhibition produces still greater anti-nociceptive effects (112,113) , and confirmed the pivotal role of 2-AG signalling in the periaqueductal grey matter (114) . The involvement of stress in human pain responses and the presence of an EC-mediated mechanism are now being studied clinically (115) .…”
Section: Supra-spinal Mechanismsmentioning
confidence: 75%
“…Detailed study of this effect revealed the mobilisation of both AEA and 2-AG in the periaqueductal grey matter (111) , and suggested that 2-AG acting at CB 1 receptors was the predominant mechanism. Additional work indicated that further enhancing stress-induced EC signalling via FAAH or MAGL inhibition produces still greater anti-nociceptive effects (112,113) , and confirmed the pivotal role of 2-AG signalling in the periaqueductal grey matter (114) . The involvement of stress in human pain responses and the presence of an EC-mediated mechanism are now being studied clinically (115) .…”
Section: Supra-spinal Mechanismsmentioning
confidence: 75%
“…Footshockinduced endocannabinoid mobilization could produce behavioral sensitization by increasing cannabinoid receptor affinity and/or by facilitating activation of signal transduction pathways. Systemically administered cannabinoids activate spinal as well as supraspinal antinociceptive mechanisms ; these mechanisms could synergize with antinociceptive effects mediated by stress-induced endocannabinoid mobilization Suplita II et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…141 Stress antinociception was associated with the heightened release of endogenous 2-AG, whereas increases in anandamide mobilization were not detected, 141 perhaps because of greater variability and lower absolute levels of anandamide in these samples. Rimonabant failed to suppress endocannabinoid SIA when administered intrathecally to rats at a dose 10 times greater than that delivered to the PAG and RVM.…”
Section: E703mentioning
confidence: 94%